Emotional Abuse Issue in Emma Donoghue’s Room - Arilia Triyoga (Universitas Ahmad Dahlan, 2020)
Room is a best-seller novel written by Emma Donoghue. It tells about a mother and her son who struggle to be free from a very wicked man, Old Nick. This novel shows violence toward a woman. This paper aims to investigate emotional abuse in Emma Donoghue's Room. This research is categorized in library research, and the data are gathered mainly from the primary source, Room. The secondary sources are from journals especially discussing domestic violence and abuse toward women. Other than that, research method books are also used to support this research. The data are found through note-taking. After that, those are classified and analyzed. The finding shows that Ma's emotional abuse is in isolation and ignorance, leading her to depression and anxiety. Old Nick isolates Ma in a tiny room, and after Ma is free from Old Nick, she is ignored by some of her family. Those experiences mainly cause ma’s depression and anxiety.